Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Loyalitas Konsumen dengan Kepuasan Konsumen Sebagai Variabel Mediasi - Devi Ardiyan Putri; Wiyadi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study investigates how service and product quality impact consumer loyalty, with a focus on the Mie Gacoan Pekalongan Branch, using quantitative methods. The target group comprises all customers of Mie Gacoan at the Pekalongan Branch. The study used purposive sampling, with 144 respondents participating. Data were collected through online questionnaires distributed via Google Forms, shared through Whatsapp and Instagram Direct. Structural Equation Modeling (SEM) with Smart Partial Least Squares (PLS) 3 software was used for data analysis. Results show that service quality and customer satisfaction positively and significantly influence consumer loyalty, whereas product quality does not have a significant impact on consumer loyalty. Both service quality and product quality positively and significantly affect consumer satisfaction. Furthermore, consumer satisfaction significantly mediates the relationship between service quality, product quality, and consumer loyalty.